Fluency in Language Assessment Literacy: A Literature Review - Sadji Evenddy, Sutrisno (Program Studi Pendidikan Bahasa Inggris, 2024)
Fluency in Language Assessment Literacy (LAL) is increasingly recognized as a crucial competency for language teachers and learners alike. This literature review explores the concept of Language Assessment Literacy, its theoretical underpinnings, and its implications for language teaching and learning. The review delves into the role of assessment literacy in language education, highlighting its impact on teaching practices, learning outcomes, and student motivation. Additionally, it examines strategies for developing and enhancing assessment literacy among language educators, including training programs and professional development initiatives. Furthermore, the review identifies current trends and future directions in language assessment literacy research, emphasizing the need for continued efforts to promote assessment literacy in language education practice and policy. Overall, this review underscores the importance of fluency in LAL and calls for concerted action to foster its development among language educators and learners.